Barbara Cartlidge and Electrum Gallery a passion for jewellery - Chadour-Sampson, Anna Beatriz 1953-; Hosegood, Janice (Arnoldsche Art Publishers, 2016)
The extraordinary life of Barbara Cartlidge (b. 1922 in Berlin) - influential gallerist, curator, jewellery artist and author - together with the history of her legendary Electrum Gallery, which she founded in 1971 with Ralph Turner in London, are documented for the first time in a single publication. Pioneers and colleagues as well as around seventy internationally renowned artists of the gallery all have their say and, in anecdotes and recollections, countless illustrations and hitherto unpublished images, tell of a strong and resolute woman and the significance of her gallery as a promoter and platform for the understanding of contemporary art jewellery. Particular attention is paid to the life of Barbara Cartlidge, who fled from Germany in 1938. For over fifty years she was a driving force in what she described as the 'the brotherhood of jewellers who make modern and thought-provoking jewellery all over the world'
Keywords: Cartlidge, Barbara -- 1922-; Electrum -- London; Geschichte; Geschichte 1955-2015; Schmuck; Design; Biografie; Bildband